Integrating Smart Apps Creator as Interactive Learning Media in Junior High School Choir Education - Chica Anggraeni; Antonius Edi Nugroho; Muhammad Asyraf Mohd Bakri (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2025)
Objective: This study aims to describe the implementation of Smart Apps Creator (SAC)–based interactive learning media in supporting choir learning at the junior high school (SMP) level. SAC enables teachers to develop interactive materials integrating images, videos, and audio to foster student engagement and active learning in music instruction. Method: This research employed a qualitative descriptive design. The participants included music teachers, students, and school stakeholders (e.g., the principal). Data were collected through classroom observations, semi-structured interviews, and document analysis of learning materials developed using SAC. The study was preceded by a brief literature review to frame key issues related to interactive media use in schools. Results and Discussion: The findings indicate that SAC-assisted learning media was implemented to deliver choir materials in a more interactive format, helping teachers organize content into accessible modules and supporting students in following vocal practice through audio-visual guidance. SAC features were perceived to increase students’ attention, learning motivation, and participation during choir activities. The implementation also revealed practical challenges, particularly differences in teachers’ digital readiness and the need for consistent instructional design to align SAC content with learning objectives. Conclusion: SAC-based interactive media is a feasible approach for enhancing choir learning in junior high schools by promoting engaging, structured, and multimedia-supported instruction. Continued teacher support and design guidance are recommended to optimize its classroom impact.